Analysis of The Use of Slang Variation by Teenagers in Selokajang Village: A Sociolinguistics Study - Winda Lestari, Oktavia; Jazeri, Mohamad; Mukhlas, Moh. (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Slang is one of the typical languages â€‹â€‹formed from Indonesian, but has been modified into a new language and is used when communicating. This study uses a research method that is descriptive qualitative method in the form of data which is then processed into a neat and easy to understand written form. This study aims to describe, validate the phenomenon under study, and to find out the reality of the phenomenon related to the use of slang by the youth of Selokajang Village. Data collection techniques used by researchers are interview techniques and also observation techniques or direct observation. Researchers used verbal data analysis techniques in the form of speeches descriptions. Data in the form of speech is based on the context of the situation, social, and cultural. Based on the results of the analysis through the interview method with the youth of Selokajang Village, it was found that there were 20 variations of slang used by the youth of Selokajang Village in daily communication. Language variation is one approach or study of sociolinguistics, language variation is often also called language variety. One form of language variation that occurs in people’s speech acts is slang or also called millennial slang.